A novel nanocomposite of NH2‐MIL‐125 modified bismaleimide‐triazine resin with excellent dielectric properties. Issue 2 (2nd August 2021) - Li, Xiaodan; Hu, Xinyu; Liu, Xiaoping; Liu, Xiaoqing; He, Rui; Liu, Hongyu; Ling, Xianzhang
Abstract: The NH2 ‐MIL‐125 nanoparticles of amino‐functionalized titanium‐based metal organic frameworks were prepared by the solvothermal method and their nanocomposites with bismaleimide‐triazine resin (BT resin) were prepared. The research results showed that NH2 ‐MIL‐125 could significantly catalyze the curing reaction of BT resin to form triazine rings, which was attributed to the synergistic catalysis the self‐polymerization of cyanate ester by the amino group and Ti 4+ in NH2 ‐MIL‐125. Because of the increase of triazine ring in crosslinking structures, the initial storage modulus of NH2 ‐MIL/BT nanocomposites improved. But the steric hindrance of NH2 ‐MIL‐125 brought the decrease on the crosslinking density and the increase on the free volume of nanocomposites. Meanwhile, besides the introduction of nanopores, the formation of more triazine rings and the increase of free volume, NH2 ‐MIL‐125 reduced the interface charge accumulation of nanocomposites through the Michael addition reaction with bismaleimide, which contributed to the reduction of dielectric constant of nanocomposites. In addition, NH2 ‐MIL‐125 with good dispersion played a toughening role and also improved the thermal stability and moisture resistance of nanocomposites. In this study, NH2 ‐MIL‐125 not only introduced nanopores but also changed crosslinking structures of BT resin, which provided a novel approach to obtain low‐dielectric materials. Abstract : In this study, NH2‐MIL‐125 not only introduced nanopores, but also changed cross‐linking structures of BT resin with catalyzing the generation of triazine ring, which provided a novel approach to obtain low‐dielectric materials.